Caracterização do sistema de produção artesanal da farinha de mandioca na comunidade indígena Tatuyo, Amazonas - Alcantara, Anne Caroline Pinheiro de (Brasil, 2022)
Due to the isolation of rural properties and the preservation of traditions, the production process of manioc flour in the Tatuyo community aims to supply their own subsistence. Its production is carried out empirically, manually, with the help of handcrafted tools produced by the community itself. This work aims to study the artisanal production process of mixed cassava flour from the Tatuyo indigenous tribe, on the left bank of the Rio Negro in the state of Amazonas, scientifically contributing to a better understanding of its production chain. Data were collected through qualitative semi-structured descriptive interviews, bibliographic and digital ethnographic survey. The cassava flour production system in the Tatuyo community is divided into twelve stages, with their respective unit operations present. The care with the forests was observed in the production process, not wearing them out in the long term, even reusing the waste generated in the processing of cassava. We conclude that by adopting completely manual production, it is important to adopt Good Flour Manufacturing Practices, to collaborate in obtaining a product with defined and durable standards.